The Certainty that Engendered New Doubts: DNA and Paternity Tests - Claudia Fonseca (Revista Estudos Feministas, 2004)
DNA paternity tests, in both private and public laboratories, have become popular of late throughout Brazil, raising some interesting questions as to the overlap of the legal and medical spheres in family issues. To analyze this question, we accompanied people involved in paternity disputes presenting their claims in the different judicial instances of Porto Alegre, RS (Defensoria, conciliation sessions, the court medical service, and the Family Court). We also examined how the different actors involved in this scenario interacted with recent Brazilian legislation dealing with paternity. On the basis of this experience, we raise the hypothesis that, far from inspiring greater tranquility, the simple existence of this test stirs up doubts. Reflecting profound repercussions for our manner of “knowing” paternal identity, reactions to the DNA test described in this paper also raise questions relevant to an anthropology of knowledge, centered on Western beliefs on science and kinship.